Respuesta :

Answer:

A

Step-by-step explanation:

f(x) = (x + 3)(x + 2)(x - 3)

The three roots are going to give - 18 so only A and D can be correct. Why minus? because at some point 3 and 2 and - 3 will all be multiplied together. When they are, the result is - 18

So why did I write x + 2 rather than x - 2? Because the roots turn an equation into 0. You are looking for a way to make x + 2 = 0. It will do that when x = - 2

which is what you were given.

Now to get the answer

(x - 3)(x + 3) = x^2 - 9

(x^2 - 9)(x + 2) = x^3 + 2x^2 - 9x - 18 = f(x)